Analisis Faktor Koagulasi : Korelasi Fibrinogen dengan Rendahnya Derajat Oksigenasi Pada Pasien COVID-19: Faktor Koagulasi Pada COVID-19 - Listyoko, Aditya Sri; Djajalaksana, Susanthy; Sugiri, Yani Jane (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Background: Hipercoagulable state is a one complication of COVID-19. The exact mechanism are still unclear, however hyperfibrinogenemia is considered one of the mechanisms for COVID-19 coagulopathy. Objective : To analyze the parameters of coagulation factors of COVID-19 patients and its correlation with degree of oxygenation Methods: We conducted an observational analytic, cross sectional, single-center study including 25 laboratory-confirmed patients in Dr. Saiful Anwar General Hospital, Malang, Indonesia from April-Juni 2020. Statistical analysis performed to determine coagulation factors like fibrinogen, D-dimer, thrombocyte and its relationship to disease severity and correlation with degree of oxygenation measured by PaO2/FiO2. Result: Subjects consisted of 12 patients (48%) in the mild-moderate group and 13 patients (52%) in severe group. D-dimer with mean 1,30 mg/L (0,43 mg/L - 4,08 mg/L) increased in 11 patients (91,67%) in mild-moderate group and 11 patients (84,61%) in severe group with mean 11,42 mg/L (0,34 mg/L – 66,30 mg/L). Fibrinogen with mean 399,73 mg/dL (235,10 mg/dL -529 mg/dL) increased in 7 patients (58,33%) in mild-moderate and 10 patients (76,92%) in severe group with mean 444,31 mg/dL (284,7 mg/dL – 543,0 mg/dL). Statistical analysis revelaed that D-dimer associated with disease severity (p=0,039) and fibrinogen was inversely correlated with degree of oxygenation measured by PaO2/FiO2 ratio with moderate correlation strength (p = 0.019; Pearson correlation = -4,67). Conclusion: High level of fibrinogen correlated with decrease of oxygenation and D-dimer associated with disease severity in hospitalized patients, suggested increasing coagulable factors such as fibrinogen and D-dimer may be the main keys developing severe condition in COVID-19 patients.